Investigating miR-9 as a mediator in laryngeal cancer health disparities - Gobin, Christina; Inkabi, Samuel; Lattimore, Chayil C.; Gu, Tongjun; Menefee, James N.; Rodriguez, Mayrangela; Kates, Heather; Fields, Christopher; Bian, Tengfei; Silver, Natalie; Xing, Chengguo; Yates, Clayton; et al. (Frontiers in Oncology, 2023)
Background: For several decades, Black patients have carried a higher burden of laryngeal cancer among all races. Even when accounting for sociodemographics, a disparity remains. Differentially expressed microRNAs have been linked to racially disparate clinical outcomes in breast and prostate cancers, yet an association in laryngeal cancer has not been addressed. In this study, we present our computational analysis of differentially expressed miRNAs in Black compared with White laryngeal cancer and further validate microRNA-9-5p (miR-9-5p) as a potential mediator of cancer phenotype and chemoresistance. Methods: Bioinformatic analysis of 111 (92 Whites, 19 Black) laryngeal squamous cell carcinoma (LSCC) specimens from the TCGA revealed miRNAs were significantly differentially expressed in Black compared with White LSCC. We focused on miR-9-5 p which had a significant 4-fold lower expression in Black compared with White LSCC (p<0.05). After transient transfection with either miR-9 mimic or inhibitor in cell lines derived from Black (UM-SCC-12) or White LSCC patients (UM-SCC-10A), cellular migration and cell proliferation was assessed. Alterations in cisplatin sensitivity was evaluated in transient transfected cells via IC50 analysis. qPCR was performed on transfected cells to evaluate miR-9 targets and chemoresistance predictors, ABCC1 and MAP1B. Results: Northern blot analysis revealed miR-9-5p was inherently lower in cell line UM-SCC-12 compared with UM-SCC-10A. UM -SCC-12 had baseline increase in cellular migration (p < 0.01), proliferation (p < 0.0001) and chemosensitivity (p < 0.01) compared to UM-SCC-10A. Increasing miR-9 in UM-SCC-12 cells resulted in decreased cellular migration (p < 0.05), decreased proliferation (p < 0.0001) and increased sensitivity to cisplatin (p < 0.001). Reducing miR-9 in UM-SCC-10A cells resulted in increased cellular migration (p < 0.05), increased proliferation (p < 0.05) and decreased sensitivity to cisplatin (p < 0.01). A significant inverse relationship in ABCC1 and MAP1B gene expression was observed when miR-9 levels were transiently elevated or reduced in either UM-SCC-12 or UM-SCC-10A cell lines, respectively, suggesting modulation by miR-9. Conclusion: Collectively, these studies suggest that low miR-9-5p may play a role in LSCC tumorigenesis and chemoresistance and may provide an avenue introducing new treatments for laryngeal cancer that may mitigate racially disparate laryngeal cancer clinical outcomes.